2021
DOI: 10.1021/acs.langmuir.1c01649
|View full text |Cite
|
Sign up to set email alerts
|

Self-Shaping Microemulsion Gels for Cultural Relic Cleaning

Abstract: Cleaning is a foundational and essential operation of protection and restoration of cultural relics, which is also the key step of follow-up works. To overcome the problems of uncontrollable diffusion of cleaning solvents and poor coverage of the cleaning solvent carriers on rough surfaces, here, we propose a strategy of using a self-shaping microemulsion gel that is prepared via emulsifying oleophilic solvents into the specific shear-thinning hydrogel structures. The gel can adaptively cover rough surfaces du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Their high surface area, tunable energy levels, and efficient charge transfer make them excellent catalysts for electrochemical reactions, enhancing reaction rates and selectivity in fuel cells and electrolysis, offering promise for clean energy technologies. Their quantum confinement effects result in tunable bandgap energies, which enable them to absorb and emit light at specific wavelengths, making them suitable for use in different applications [47,48] . SQD‐modified LDHs represent a novel hybrid material.…”
Section: Synthesis Designing and Morphological Characterization Of La...mentioning
confidence: 99%
See 1 more Smart Citation
“…Their high surface area, tunable energy levels, and efficient charge transfer make them excellent catalysts for electrochemical reactions, enhancing reaction rates and selectivity in fuel cells and electrolysis, offering promise for clean energy technologies. Their quantum confinement effects result in tunable bandgap energies, which enable them to absorb and emit light at specific wavelengths, making them suitable for use in different applications [47,48] . SQD‐modified LDHs represent a novel hybrid material.…”
Section: Synthesis Designing and Morphological Characterization Of La...mentioning
confidence: 99%
“…The research society has shown immense interest in utilizing the fullerenes dots for the fabrication of heterostructure material because of its unresolved physicochemical characteristics and stability. The incorporation of Fullerene QD into the LDH network could produce new attuned interfacial active sites consequently accelerating the electronic transfer between both LDH and Fullerene QD materials, thus improving the electrocatalytic properties of the nanohybrid material [47–49] By taking this fact, Wang et al. designed a novel nano heterostructure composed of fullerene quantum dot anchored on a CoNi LDH nanosheet array self–supported on porous Ni foam (FQD/CoNi−LDH/NF) through a self–assembly hydrothermal method.…”
Section: Synthesis Designing and Morphological Characterization Of La...mentioning
confidence: 99%
“…Wolbers initially used polyacrylic acid as a gelling agent to eliminate dust and coatings from the surface of oil paintings [ 23 ]. Subsequently, hydrogels were used for the purpose of cleaning stone surfaces [ 24 ], metal [ 25 ], frescoes [ 26 ], and other artifacts. The sol–gel transition is a significant characteristic of hydrogels, allowing the formation of bonding interfaces with different materials [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various gelling agents such as carrageenan, gellan gum, isubgol, xanthan gum, and carbomer have been used to optimize the viscosity of the formulations and thus increase the retention time and efficiency, thereby resulting in a faster release of the drug compared to the available conventional formulations. [28][29][30][31][32][33]76,77 In this study, functional nanoparticles of Clotrimazole-loaded microemulsified gels (CTZ-μEGs) were prepared using the biocompatible components and further evaluated for an in vitro permeation release study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this way, it minimizes the barrier function of the stratum corneum and opens a pore or passage for the active ingredient to be transported through the skin, which further increases the permeability of the active ingredient. The main problem associated with μE-based drug delivery is low viscosity, which leads to lower drug retention. Various gelling agents such as carrageenan, gellan gum, isubgol, xanthan gum, and carbomer have been used to optimize the viscosity of the formulations and thus increase the retention time and efficiency, thereby resulting in a faster release of the drug compared to the available conventional formulations. ,, In this study, functional nanoparticles of Clotrimazole-loaded microemulsified gels (CTZ-μEGs) were prepared using the biocompatible components and further evaluated for an in vitro permeation release study.…”
Section: Introductionmentioning
confidence: 99%